2015
DOI: 10.1186/s40478-015-0218-y
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptide repeat protein inclusions are rare in the spinal cord and almost absent from motor neurons in C9ORF72 mutant amyotrophic lateral sclerosis and are unlikely to cause their degeneration

Abstract: IntroductionCytoplasmic TDP-43 inclusions are the pathological hallmark of amyotrophic lateral sclerosis (ALS) and tau-negative frontotemporal lobar dementia (FTLD). The G4C2 repeat mutation in C9ORF72 is the most common cause of ALS and FTLD in which, in addition to TDP-43 inclusions, five different di-peptide repeat (DPR) proteins have been identified. Di-peptide repeat proteins are translated in a non-canonical fashion from sense and antisense transcripts of the G4C2 repeat (GP, GA, GR, PA, PR). DPR inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 23 publications
5
72
1
Order By: Relevance
“…In at least one study, the RAN translation protein products and aberrant increase of proteasome marker p62 are not consistently detected (Sareen et al, 2013). These results have also been further extended by another recent study (Gomez-Deza et al, 2015), which shows a distinct lack of RAN translation protein products in spinal motor neurons in FALS patients with C9ORF72 mutations. In the future, it will be important to use the iPSC models to determine how RAN proteins induce p62 pathology and whether p62 pathology is causally linked to neuronal degeneration and functional deficits.…”
Section: Induced Pluripotent Stem Cells (Ipscs) As Models For Alssupporting
confidence: 69%
See 1 more Smart Citation
“…In at least one study, the RAN translation protein products and aberrant increase of proteasome marker p62 are not consistently detected (Sareen et al, 2013). These results have also been further extended by another recent study (Gomez-Deza et al, 2015), which shows a distinct lack of RAN translation protein products in spinal motor neurons in FALS patients with C9ORF72 mutations. In the future, it will be important to use the iPSC models to determine how RAN proteins induce p62 pathology and whether p62 pathology is causally linked to neuronal degeneration and functional deficits.…”
Section: Induced Pluripotent Stem Cells (Ipscs) As Models For Alssupporting
confidence: 69%
“…Similarly, another study indicated that C9ORF72 iPSC-derived neurons show reduced viability when exposed to chloroquine, an inhibitor that blocks the autophagy pathway (Almeida et al, 2013). Finally, C9ORF72 iPSC-derived neurons should also provide a convenient tool to investigate the potential loss-of-function effect of C9ORF72 gene product in the regulation of endosomal trafficking and in the pathogenesis of TDP-43 proteinopathy, which are common neuropathological features in these cases (Farg et al, 2014; Gomez-Deza et al, 2015). …”
Section: Induced Pluripotent Stem Cells (Ipscs) As Models For Alsmentioning
confidence: 99%
“…The lower limb onset of ALS symptoms may mask or make it difficult to elicit spinocerebellar features in these cases. Importantly, lower limb onset of itself in other ALS cases (sporadic and C9ORF72) does not predispose Purkinje cells to retrograde degeneration, and neither does having another type of repeat expansion (despite increased cerebellar pathology with C9ORF72 expansions; present study and previous works 5,23 ). Interestingly, both ATXN2 and C9ORF72 expansion-specific proteins do not accumulate in motor neurons (present study and previous works 5,23 ) with abnormal ATXN2 accumulation also not observed in Purkinje cells in any of the ALS cases with the expansion (present study and see Table 5).…”
Section: Annals Of Neurologymentioning
confidence: 54%
“…While toxicity of DPRs has been shown in model organisms and cell culture (Wen et al 2014;Lopez-Gonzalez et al 2016), this could reflect nonphysiological effects resulting from overexpression. Understanding how DPRs are made (Green et al 2016) and how abundant they truly are in degenerating regions (Gomez-Deza et al 2015) will be important in order to gauge how critical they are to the pathology of the ALS/FTD spectrum.…”
Section: Rna-centric Mechanisms In C9orf72 Als-ftdmentioning
confidence: 99%